A Particle Swarm Optimization-PID controller of a DC Servomotor for Multi-Fingered Robot Hand - Tarmizi, W.F. (Institute of Electrical and Electronics Engineers Inc., 2017)
In the construction of robot applications, controller is very important in producing good performance the robot system. This paper presents the modeling and simulation of multi fingered robot hand (MFRH) with the conventional and modern controllers where the output responses have been analyzed. A swarm algorithm known as Particle Swarm Optimization (PSO) has been used to find optimum solutions in a large search space. Simulation of modern controller (PSO-PID) has produced better results than the conventional controller in terms of system parameters such as rise time, settling time steady state error and maximum overshoot in the DC Servomotor speed control MFRH. © 2016 IEEE.